1992
DOI: 10.1073/pnas.89.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Murine B7 antigen provides an efficient costimulatory signal for activation of murine T lymphocytes via the T-cell receptor/CD3 complex.

Abstract: We demonstrate that the murine B7 (mB7) protein is a potent costimulatory molecule for the activation of resting murine CD4+ T cells through the T-cell receptor (TCR)/CD3 complex. Stable mB7-transfected Chinese hamster ovary cells, but not vector-transfected controls, synergize with anti-CD3 monoclonal antibody and Con A-induced T-cell activation, resulting ultimately in proliferation. mB7 exerted its effect by inducing production of interleukin 2 and expression of the interleukin 2 receptor. Thus, mB7 costimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 41 publications
2
68
1
Order By: Relevance
“…Thy-1-driven T cell proliferation similarly depended on both B7-1-and B7-2-mediated costimulation. Our results are in stark contrast with an earlier report that relatively inefficient CD4 Ï© T cell proliferation and IL-2 synthesis occur in response to the G7 anti-Thy-1 mAb in a xenogeneic system that used B7-transfected Chinese hamster ovary cells as accessory cells (42). However, because B7-2 was not identified at the time, the failure of B7-1-transfected Chinese hamster ovary cells to optimally costimulate Thy-1-driven responses could be at least in part due to a lack of CD28-B7-2 interactions.…”
Section: Discussioncontrasting
confidence: 56%
“…Thy-1-driven T cell proliferation similarly depended on both B7-1-and B7-2-mediated costimulation. Our results are in stark contrast with an earlier report that relatively inefficient CD4 Ï© T cell proliferation and IL-2 synthesis occur in response to the G7 anti-Thy-1 mAb in a xenogeneic system that used B7-transfected Chinese hamster ovary cells as accessory cells (42). However, because B7-2 was not identified at the time, the failure of B7-1-transfected Chinese hamster ovary cells to optimally costimulate Thy-1-driven responses could be at least in part due to a lack of CD28-B7-2 interactions.…”
Section: Discussioncontrasting
confidence: 56%
“…In vitro studies have demonstrated that CD28 is the surface receptor of a cyclosporin A-resistant T-cell signal transduction pathway (10). Stimulation of CD28 by its natural ligand B7 provides costimulation to TCR-activated T cells, leading to proliferation and lymphokine gene expression (4,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The best-defined costimulatory system in T ceil activation is that involving B7-CD28 interactions (23,(49)(50)(51)(52)(53)(54)(55). There are two reasons why it is unlikely that the absence or presence of B7 is playing a significant role in the T cell functional responses described here.…”
Section: Discussionmentioning
confidence: 94%